The family Onychiuridae (Collembola) from karst caves of the Basque biospeleologic district, with description of four new species - Beruete, Enrique; Arbea, Javier I.; Baquero, Enrique; Jordana, Rafael (Zootaxa, 2021)
The study of Onychiuridae from 42 caves of the north of the Iberian Peninsula and southwestern France has revealed the existence of 32 species inhabiting the caves of the Basque bio-speleological district, among which four new species are described: Deuteraphorura bizkaiensis sp. nov., Deuteraphorura bolivari sp. nov., Onychiurus arbailakensis sp. nov. and Protaphorura leitzaldeaensis sp. nov. Furthermore, three species, Deuteraphorura boneti (Gisin, 1953), Deuteraphorura akelaris (Jordana & Beruete, 1983) and Spinonychiurus vandeli (Cassagnau, 1960), are redescribed based on type and new material to furnish the description of some characters, especially concerning the chaetotaxy, not considered in the original description. Keys to the recorded species are also reported.